Mediation as an anthroposociocultural value - Yuriichuk, Illia; Havrylyuk, Ruslana; Patsurkivskyy, Petro (European Journal of Law and Public Administration, 2020)
The article examines the phenomenon of mediation as a value of a developed civil society from the ideological and methodological positions of the anthroposociocultural approach. The general historical conditions of the emergence of mediation and its anthroposociocultural code, paradigmatic types of mediation and the most important properties of each of them are analyzed. The article reveals the value nature of mediation as a Copernican revolution in ideology and methods of constructive resolution of conflicts between individuals and their communities. The conclusions are substantiated that: mediation belongs to the genus of anthroposociocultural values as their qualitatively distinguished type; mediation is functionally related to fundamental universal human values - human rights, the rule of law and pluralistic democracy - as a tool for their protection by human beings themselves in the form of a joint solution of interpersonal conflicts by their own carriers with the help of professional mediators; modern science distinguishes at least two paradigmatically different types of mediation - traditional mediation and narrative mediation; mediation of the first type as a value is applied mainly to the solution of interpersonal conflicts, and mediation of the second type is mainly applied to the solution of conflicts between human communities in polyidentical societies.
Keywords: mediation; value; anthroposocicultural mediation code; traditional mediation; narrative mediation